Molecular Epidemiological Surveillance of CTX-M-15-producing Klebsiella pneumoniae from the patients of a teaching hospital in Sindh, Pakistan. [version 3; peer review: 3 approved] - Muzaheed Muzaheed (F1000 Research Ltd, 2021)
Background  The presence of Extended-spectrum β-lactamase positive bacteria in hospital setting is an aggravating influential factor for hospitalized patients, and its consequences may be hazardous. Therefore, there is a need for rapid detection methods for newly emerging drug-resistant bacteria. This study was aimed at the molecular characterization of Extended-spectrum β-lactamase -positive  Klebsiella pneumoniae isolates recovered from the patients of a teaching hospital in Sindh, Pakistan.   Methods  A total of 513  K. pneumoniae isolates were obtained from various clinical samples during June 2019 to May 2020. The collected isolates were investigated for antimicrobial susceptibility (antibiogram), and PCR and DNA sequencing were performed to analyse the ESBL genes.   Results  Among the 513 isolates, as many as 359 (69.9%) were Extended-spectrum β-lactamase producers and 87.5% were multi-drug resistant, while none had resistance to imipenem. PCR scored 3% blaTEM, 3% blaSHV, and 60% blaCTX-M-15 genes for the tested isolates.   Conclusion  The study showed that CTX-M-15 was the major prevalent Extended-spectrum β-lactamase type among the isolates. Additionally, all the isolates were susceptible to carbapenems. Screening and detection of Extended-spectrum β-lactamase tests are necessary among all isolates from the enterobacteriaceae family in routine microbiology laboratory to prevent associated nosocomial infections. A larger study is essential to understand molecular epidemiology of Extended-spectrum β-lactamase producing organisms to minimize morbidities due to these multidrug resistant organisms.